2022
DOI: 10.2147/opth.s340386
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Patient Tolerability of Omidenepag Isopropyl in the Treatment of Glaucoma and Ocular Hypertension

Abstract: Current therapeutic approaches for glaucoma aim to reduce intraocular pressure (IOP), which is the only available and reliable strategy proven to control the risk of disease development and progression. Omidenepag isopropyl (OMDI) is a novel topical ocular hypotensive agent that was launched onto the market for the treatment of glaucoma and ocular hypertension (OHT). After topical instillation and during corneal penetration, OMDI is converted into the active metabolite omidenepag (OMD), which behaves as a non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 64 publications
(120 reference statements)
0
21
0
Order By: Relevance
“…OMDI 0.002% was non-inferior to latanoprost 0.005% in reducing IOP in glaucoma patients [ 27 ], therefore has been used as a first-line medication. Because of the possible risk of macular edema, OMDI is contraindicated in patients with pseudophakic eyes [ 28 ]. This is a possible explanation of the unique distribution of PGEP 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OMDI 0.002% was non-inferior to latanoprost 0.005% in reducing IOP in glaucoma patients [ 27 ], therefore has been used as a first-line medication. Because of the possible risk of macular edema, OMDI is contraindicated in patients with pseudophakic eyes [ 28 ]. This is a possible explanation of the unique distribution of PGEP 2 .…”
Section: Discussionmentioning
confidence: 99%
“…This is a possible explanation of the unique distribution of PGEP 2 . OMDI reduces IOP by enhancing both conventional trabecular and uveoscleral outflow facilities without prostaglandin-associated periorbitopathy (PAP) seen with PGF 2α [ 28 , 29 ]. By switching from PGF 2α to OMDI, signs of PAP were improved within 3 months after the switching [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…35 The incidences of OMDI-related adverse effects typically reported in clinical studies have been conjunctival hyperemia (19.7%), corneal thickening (5%), macular edema (4.4%), ocular pain (3.6%), glare (3.3%), blurred vision (1.7%), and anterior chamber inflammation (1.4%). 36 Hyperemia is a known side effect of PG analogs, occurring immediately following administration and disappearing after several hours. 37 OMDI, a PGE2 agonist, is also a kind of PG analog, so it is reasonable to assume that a similar pattern would be observed.…”
Section: Discussionmentioning
confidence: 99%
“…It is a relatively selective agonist of the prostaglandin E 2 (EP2) receptor approved to reduce intraocular pressure in patients with open-angle glaucoma or ocular hypertension. Clinical trials have demonstrated that omidenepag reduces intraocular pressure by enhancing outflow without complications (Aihara et al 2021 ; Matsuo et al 2022 ). The most frequent adverse reactions are conjunctival hyperemia, photophobia, vision blurred, dry eye, instillation site pain, and visual impairment.…”
Section: Othermentioning
confidence: 99%